A presença do corpo feminino como objeto na arte contemporânea: as artistas contemporâneas e suas autorias - Vieira, Carla Borin (2010)
This search presents reflections on the female body as an object in the contemporary art and some enquiries within history that led to this denomination. Through this, it was noted the importance of the role of women in society that led the images of your body dressed result in social transformations and in Visual Arts. With these questionings, I put in question the symptoms that are present in contemporary art related to the female body and I exemplify with works of women artists that discuss their own body stripped within contemporary society. To address issues on the body alive in art, the artists make questions about body art, the trivialization of women's image, sharp and seductive objects, performance and technology, placing the female body in debate.